1999
DOI: 10.1300/j096v06n01_02
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural Chemical Safety Training Materials for Farmworkers

Abstract: Preventing or reducing exposure to agricultural chemicals is an important focus for health educators serving migrant and seasonal farmworkers and their families. The development of the US Environmental Protection Agency Worker Protection Standard requiring that farmworkers receive pesticide-related training created a demand for culturally appropriate and effective training materials, yet no compendium of such materials exists. This paper reports the results of a search for and evaluation of training materials … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 7 publications
(6 reference statements)
0
16
0
Order By: Relevance
“…Quandt and colleagues54 evaluated the materials developed to provide WPS training and found that improvement was needed to make them culturally and educational appropriate; this evaluation of WPS materials needs to be updated. Whalley and colleagues53 found that even among workers who have received pesticide safety training, about one-quarter did not understand the training they received.…”
Section: Documentation Of Safety Training Provided To Agricultural Womentioning
confidence: 99%
See 1 more Smart Citation
“…Quandt and colleagues54 evaluated the materials developed to provide WPS training and found that improvement was needed to make them culturally and educational appropriate; this evaluation of WPS materials needs to be updated. Whalley and colleagues53 found that even among workers who have received pesticide safety training, about one-quarter did not understand the training they received.…”
Section: Documentation Of Safety Training Provided To Agricultural Womentioning
confidence: 99%
“…However, translating training materials does not ensure that they are literacy, language, or culturally appropriate. As Quandt and colleagues54 report in their evaluation of materials developed to provide WPS training, many such materials needed substantial improvement to make them linguistically, culturally, and educationally appropriate. Training materials developed and distributed by advocacy and service organizations and university programs are readily available for review and evaluation.…”
Section: Industry Response To the Issuementioning
confidence: 99%
“…They have used their networks to farmworker groups across the country to locate existing intervention materials, and they have participated in the project's critical review of these. 33 A partnership with the NCFP was also important in developing the intervention. A series of meetings of the university researchers, the project coordinator, and the NCFP staff were held to develop the components of the intervention.…”
Section: Partnership With a Community-based Organizationmentioning
confidence: 99%
“…In general these materials are prescriptive, telling farmworkers how to behave, but they fail to tell how such behaviors will reduce risk (27).…”
mentioning
confidence: 99%